Golf ball
The golf ball design with a core, intermediate layer, and zinc ion-neutralized ionomer resin cover addresses moldability and scratch resistance issues, enhancing spin and flight performance by balancing cover hardness and thickness.
Patent Information
- Application Number
- JP2023115322
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-13
- Publication Date
- 2025-01-24
AI Technical Summary
Golf balls with soft covers for enhanced spin performance suffer from poor flight performance and moldability issues, while thin covers are difficult to mold and lack scratch resistance.
A golf ball design featuring a core, an intermediate layer made of ionomer resin, and a cover with specific hardness and thickness ratios, using zinc ion-neutralized ionomer resin to balance spin, flight, and moldability, with a cover hardness of 50 Shore D or less and a thickness that allows for easy molding.
The design achieves excellent spin performance, flight performance, and scratch resistance while maintaining moldability, with a flexible cover that does not inhibit repulsion performance despite its softness.
Smart Images

Figure 2025012468000001_ABST
Abstract
Description
[Technical field]
[0001] The present specification discloses a golf ball having a core, an intermediate layer and a cover. [Background technology]
[0002] A typical golf ball has a core, an intermediate layer, and a cover. Ionomer resin is known as a material for the cover. JP 2023-4542 A discloses a golf ball having a cover whose base resin is an ionomer. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent Publication No. 2023-4542 Summary of the Invention [Problem to be solved by the invention]
[0004] Golf players place importance on the controllability of a golf ball. This controllability correlates with spin performance. The higher the backspin speed, the smaller the run. By using a golf ball that generates high-speed backspin, a player can make the golf ball stop at a target point. If the side spin speed is high, the golf ball is likely to curve. By using a golf ball that generates high-speed side spin, a player can intentionally curve the golf ball.
[0005] A soft cover can contribute to a high spin rate. A golf ball using this cover has excellent controllability. However, this cover impairs the resilience of the golf ball. A golf ball with insufficient resilience has poor flight performance. The use of a thin cover can suppress the adverse effect of the cover on flight performance. However, molding a thin cover is difficult. A soft cover also has poor abrasion resistance.
[0006] The applicant's intention is to provide a golf ball which is excellent in spin performance, flight performance, moldability and scuff resistance. [Means for solving the problem]
[0007] The golf ball disclosed in this specification has a core, an intermediate layer located outside the core and made of a resin composition, and a cover located outside the intermediate layer and made of another resin composition. The hardness Hc (Shore D) of the cover is 50 or less. The main component of the base resin of the resin composition of the intermediate layer is an ionomer resin. The main component of the base resin of the resin composition of the cover is an ionomer resin. The amount P(I) of the ionomer resin in the base resin of the cover is 60 parts by mass or more per 100 parts by mass of the base resin. The amount P(Na) of the sodium ion-neutralized ionomer resin in the base resin of the cover is 5 parts by mass or less per 100 parts by mass of the base resin. This golf ball satisfies the following mathematical expressions (1) and (2). Fm / (Hm * Tm) - Fc / (Hc * Tc) ≧ 3.0 (1) Mc*Tc ≧ 10.0 (2) Hm: Hardness of the middle layer (Shore D) Tm: thickness of the middle layer (mm) Fm: Bending stiffness of the middle layer (Mpa) Tc: Cover thickness (mm) Fc: Bending rigidity of the cover (Mpa) Mc: Melt flow rate (g / 10min) of the cover at a temperature of 190°C and a load of 2.16 kg Effect of the Invention
[0008] The cover of this golf ball is flexible. Therefore, this golf ball has excellent spin performance in approach shots. Since the amount P(Na) of the sodium ion neutralized ionomer resin is small, this cover has excellent abrasion resistance even though it is soft. Since the resin of this cover has excellent fluidity, it can contribute to the moldability of the cover. Even if the cover is thin, this cover can be easily molded. Even if the cover is thin and soft, it does not hinder the resilience performance of the golf ball.
[0009] This golf ball is excellent in spin performance, flight performance, moldability and scuff resistance. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a partially cutaway cross-sectional view showing a golf ball according to one embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, preferred embodiments will be described in detail with reference to the drawings as appropriate.
[0012] 1 has a spherical core 4, an intermediate layer 6 located on the outside of the core 4, and a cover 8 located on the outside of the intermediate layer 6. The golf ball 2 has a plurality of dimples 10 on its surface. The portion of the surface of the golf ball 2 other than the dimples 10 is land 12. The golf ball 2 has a paint layer and a mark layer on the outside of the cover 8, but these layers are omitted from the illustration.
[0013] The diameter of the golf ball 2 is preferably 40 mm or greater and 45 mm or less. From the viewpoint of satisfying the standards of the United States Golf Association (USGA), the diameter is particularly preferably 42.67 mm or greater. From the viewpoint of suppressing air resistance, the diameter is more preferably 44 mm or less, and particularly preferably 42.80 mm or less.
[0014] The mass of the golf ball 2 is preferably 40 g or greater and 50 g or less. From the viewpoint of obtaining a large inertia, the mass is more preferably 44 g or greater, and particularly preferably 45.00 g or greater. From the viewpoint of satisfying the USGA standard, the mass is particularly preferably 45.93 g or less.
[0015] The core 4 is formed by crosslinking a rubber composition. Examples of preferred base rubbers include polybutadiene, polyisoprene, styrene-butadiene copolymer, ethylene-propylene-diene copolymer, and natural rubber. From the viewpoint of the resilience performance of the golf ball 2, polybutadiene is preferred. When polybutadiene is used in combination with other rubber, it is preferred that polybutadiene be the main component. Specifically, the ratio of polybutadiene to the entire base rubber is preferably 50% by mass or more, more preferably 70% by mass or more, and particularly preferably 80% by mass or more. Polybutadiene having a ratio of cis-1,4 bonds of 80% or more is particularly preferred.
[0016] The rubber composition of the core 4 preferably contains a co-crosslinking agent. From the viewpoint of durability and resilience performance of the golf ball 2, a preferred co-crosslinking agent is a monovalent or divalent metal salt of an α,β-unsaturated carboxylic acid having 2 to 8 carbon atoms. Preferred co-crosslinking agents include zinc acrylate, magnesium acrylate, zinc methacrylate, and magnesium methacrylate. Zinc acrylate and zinc methacrylate are particularly preferred.
[0017] The rubber composition may contain an α,β-unsaturated carboxylic acid having 2 to 8 carbon atoms and a metal oxide. The two react in the rubber composition to obtain a salt. The salt functions as a co-crosslinking agent. Preferred α,β-unsaturated carboxylic acids include acrylic acid and methacrylic acid. Preferred metal oxides include zinc oxide and magnesium oxide.
[0018] The amount of the co-crosslinking agent is preferably 10 parts by mass or more and 45 parts by mass or less per 100 parts by mass of the base rubber. Golf ball 2 having this amount of 10 parts by mass or more has excellent resilience performance. From this viewpoint, this amount is more preferably 15 parts by mass or more, and particularly preferably 20 parts by mass or more. Golf ball 2 having this amount of 45 parts by mass or less has excellent shot feeling. From this viewpoint, this amount is more preferably 40 parts by mass or less, and particularly preferably 35 parts by mass or less.
[0019] Preferably, the rubber composition of the core 4 contains an organic peroxide. The organic peroxide functions as a crosslinking initiator. The organic peroxide contributes to the durability and resilience performance of the golf ball 2. Examples of suitable organic peroxides include dicumyl peroxide, 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, and di-t-butyl peroxide. A particularly versatile organic peroxide is dicumyl peroxide.
[0020] The amount of organic peroxide is preferably 0.1 parts by weight or more and 3.0 parts by weight or less per 100 parts by weight of the base rubber. Golf ball 2 having this amount of 0.1 parts by weight or more has excellent resilience performance. From this viewpoint, this amount is more preferably 0.3 parts by weight or more, and particularly preferably 0.5 parts by weight or more. Golf ball 2 having this amount of 3.0 parts by weight or less has excellent shot feeling. From this viewpoint, this amount is more preferably 2.5 parts by weight or less, and particularly preferably 2.0 parts by weight or less.
[0021] Preferably, the rubber composition of the core 4 contains an organic sulfur compound. The organic sulfur compound contributes to the resilience performance of the golf ball 2. The organic sulfur compound includes a naphthalene thiol-based compound, a benzenethiol-based compound, and a disulfide-based compound.
[0022] Examples of naphthalene-based compounds include 1-naphthalene-thiol, 2-naphthalene-thiol, 4-chloro-1-naphthalene-thiol, 4-bromo-1-naphthalene-thiol, 1-chloro-2-naphthalene-thiol, 1-bromo-2-naphthalene-thiol, 1-fluoro-2-naphthalene-thiol, 1-cyano-2-naphthalene-thiol, and 1-acetyl-2-naphthalene-thiol, as well as metal salts thereof. A preferred metal salt is zinc salt.
[0023] Examples of benzenethiol compounds include benzenethiol, 4-chlorobenzenethiol, 3-chlorobenzenethiol, 4-bromobenzenethiol, 3-bromobenzenethiol, 4-fluorobenzenethiol, 4-iodobenzenethiol, 2,5-dichlorobenzenethiol, 3,5-dichlorobenzenethiol, 2,6-dichlorobenzenethiol, 2,5-dibromobenzenethiol, 3,5-dibromobenzenethiol, 2-chloro-5-bromobenzenethiol, 2,4,6-trichlorobenzenethiol, 2,3,4,5,6-pentachlorobenzenethiol, 2,3,4,5,6-pentafluorobenzenethiol, 4-cyanobenzenethiol, 2-cyanobenzenethiol, 4-nitrobenzenethiol and 2-nitrobenzenethiol, as well as their metal salts.Preferred metal salt is zinc salt.
[0024] Disulfide compounds include diphenyl disulfide, bis(4-chlorophenyl) disulfide, bis(3-chlorophenyl) disulfide, bis(4-bromophenyl) disulfide, bis(3-bromophenyl) disulfide, bis(4-fluorophenyl) disulfide, bis(4-iodophenyl) disulfide, bis(4-cyanophenyl) disulfide, bis(2,5-dichlorophenyl) disulfide, bis(3,5-dichlorophenyl) disulfide, bis(2,6-dichlorophenyl) disulfide, and bis(2,5-dibutyl). Examples of such disulfides include bis(3,5-dibromophenyl) disulfide, bis(2-chloro-5-bromophenyl) disulfide, bis(2-cyano-5-bromophenyl) disulfide, bis(2,4,6-trichlorophenyl) disulfide, bis(2-cyano-4-chloro-6-bromophenyl) disulfide, bis(2,3,5,6-tetrachlorophenyl) disulfide, bis(2,3,4,5,6-pentachlorophenyl) disulfide and bis(2,3,4,5,6-pentabromophenyl) disulfide.
[0025] The amount of the organic sulfur compound is preferably 0.1 parts by weight or more and 1.5 parts by weight or less per 100 parts by weight of the base rubber. When this amount is 0.1 parts by weight or more, the golf ball 2 has excellent resilience performance. From this viewpoint, this amount is more preferably 0.2 parts by weight or more, and particularly preferably 0.3 parts by weight or more. When this amount is 1.5 parts by weight or less, the golf ball 2 has excellent shot feeling. From this viewpoint, this amount is more preferably 1.3 parts by weight or less, and particularly preferably 1.1 parts by weight or less. Two or more organic sulfur compounds may be used in combination.
[0026] The rubber composition of the core 4 may contain a filler for the purpose of adjusting the specific gravity, etc. Examples of suitable fillers include zinc oxide, barium sulfate, calcium carbonate, and magnesium carbonate. The amount of the filler is appropriately determined so that the intended specific gravity of the core 4 is achieved.
[0027] The rubber composition of the core 4 may contain appropriate amounts of various additives such as sulfur, carboxylic acid, carboxylate, antioxidant, colorant, plasticizer, dispersant, etc. This rubber composition may contain crosslinked rubber powder or synthetic resin powder.
[0028] The diameter of the core 4 is preferably 35.0 mm or greater and 40.5 mm or less. A golf ball 2 having a core 4 with a diameter of 35.0 mm or greater has excellent resilience performance. From this viewpoint, the diameter is more preferably 36.0 mm or greater, and particularly preferably 36.5 mm or greater. A golf ball 2 having a core 4 with a diameter of 40.5 mm or less has excellent durability. From this viewpoint, the diameter is more preferably 40.0 mm or less, and particularly preferably 39.5 mm or less.
[0029] The amount of deformation Dc of the core 4 is preferably 3.0 mm or more and 5.0 mm or less. A golf ball 2 having a core 4 with a amount of deformation Dc of 3.0 mm or more has an excellent shot feeling. From this viewpoint, the amount of deformation Dc is more preferably 3.5 mm or more, and particularly preferably 3.8 mm or more. A golf ball 2 having a core 4 with a amount of deformation Dc of 5.0 mm or less has excellent resilience performance. From this viewpoint, the amount of deformation Dc is more preferably 4.7 mm or less, and particularly preferably 4.5 mm or less.
[0030] The amount of compressive deformation Dc is measured using a Yamada compression tester "SCH." In this tester, the core 4 is placed on a metal hard plate. A metal cylinder is gradually lowered towards the core 4. The core 4, which is sandwiched between the bottom of the cylinder and the hard plate, is deformed. The distance traveled by the cylinder from when an initial load of 98N is applied to the core 4 until a final load of 1274N is applied is measured. The speed of travel of the cylinder until the initial load is applied is 0.83mm / s. The speed of travel of the cylinder from when the initial load is applied to when the final load is applied is 1.67mm / s.
[0031] The center hardness Ho of the core 4 is preferably 40 or greater and 65 or less. A golf ball 2 having a core 4 with a center hardness Ho of 40 or greater has excellent resilience performance. From this viewpoint, the center hardness Ho is more preferably 45 or greater, and particularly preferably 47 or greater. A golf ball 2 having a core 4 with a center hardness Ho of 65 or less has an excellent shot feeling. From this viewpoint, the center hardness Ho is more preferably 60 or less, and particularly preferably 55 or less.
[0032] The center hardness Ho is measured by a Shore C hardness tester attached to an automatic hardness tester (H. Burleith Co., Ltd., product name "Digitest II"). The hardness tester is pressed against the center of a cross section of a hemisphere obtained by cutting the golf ball 2. The measurement is performed in an environment of 23°C.
[0033] The surface hardness Hs of the core 4 is preferably 70 or greater and 95 or less. A golf ball 2 having a core 4 with a surface hardness Hs of 70 or greater has excellent resilience performance. From this viewpoint, the surface hardness Hs is more preferably 75 or greater, and particularly preferably 77 or greater. A golf ball 2 having a core 4 with a surface hardness Hs of 95 or less has an excellent shot feeling. From this viewpoint, the surface hardness Hs is more preferably 90 or less, and particularly preferably 85 or less.
[0034] The surface hardness Hs is measured by a Shore C type hardness tester attached to an automatic hardness tester ("Digitest II" product name, manufactured by H. Burleith Co., Ltd.). The hardness tester is pressed against the surface of the core 4. The measurement is performed in an environment of 23°C.
[0035] The difference (Hs-Ho) between the surface hardness Hs and the center hardness Ho is preferably 28 or greater. A golf ball 2 having a core 4 with a difference (Hs-Ho) of 28 or greater suppresses spin upon shots with a driver. This golf ball 2 has excellent flight performance upon shots with a driver. In this respect, the difference (Hs-Ho) is more preferably 29 or greater, and particularly preferably 30 or greater. In terms of durability of the golf ball 2, the difference (Hs-Ho) is preferably 35 or less, more preferably 34 or less, and particularly preferably 33 or less.
[0036] The intermediate layer 6 is located outside the core 4. In this embodiment, the intermediate layer 6 is in contact with the core 4. The intermediate layer 6 is molded from a resin composition. In this embodiment, the intermediate layer 6 is molded from a thermoplastic resin composition. Examples of the base polymer of this resin composition include ionomer resin, thermoplastic polyester elastomer, thermoplastic polyamide elastomer, thermoplastic polyurethane elastomer, thermoplastic polyolefin elastomer, and thermoplastic polystyrene elastomer. In particular, ionomer resin is preferable. Ionomer resin has high elasticity. A golf ball 2 having an intermediate layer 6 containing an ionomer resin has excellent resilience performance. This golf ball 2 has excellent flight performance in driver shots.
[0037] The ionomer resin may be used in combination with other resins. In such a case, the ionomer resin is used as the main component of the base resin from the viewpoint of resilience performance. The amount of the ionomer resin in the base resin of the mid layer 6 is preferably 50 parts by mass or more, more preferably 60 parts by mass or more, and particularly preferably 70 parts by mass or more, per 100 parts by mass of the base resin.
[0038] Preferred ionomer resins include binary ionomer resins and ternary ionomer resins. The binary ionomer resins are binary copolymers of an α-olefin and an α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms, and at least a part of the carboxyl groups of the copolymer are neutralized with metal ions. The preferred binary ionomer resins contain 80% to 90% by mass of an α-olefin and 10% to 20% by mass of an α,β-unsaturated carboxylic acid. The binary ionomer resins are excellent in resilience performance. The ternary ionomer resins are ternary copolymers of an α-olefin, an α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms, and an α,β-unsaturated carboxylic acid ester having 2 to 22 carbon atoms, and at least a part of the carboxyl groups of the copolymer are neutralized with metal ions. A preferred ternary ionomer resin contains 70% by mass or more and 85% by mass or less of an α-olefin, 5% by mass or more and 30% by mass or less of an α,β-unsaturated carboxylic acid, and 1% by mass or more and 25% by mass or less of an α,β-unsaturated carboxylic acid ester. This ternary ionomer resin has excellent resilience performance. In the binary ionomer resin and the ternary ionomer resin, the preferred α-olefin is ethylene and propylene, and the preferred α,β-unsaturated carboxylic acid is acrylic acid and methacrylic acid. A particularly preferred ionomer resin is a copolymer of ethylene and acrylic acid, in which at least a part of the carboxyl group of this copolymer is neutralized with a metal ion. Another particularly preferred ionomer resin is a copolymer of ethylene and methacrylic acid, in which at least a part of the carboxyl group of this copolymer is neutralized with a metal ion.
[0039] Examples of metal ions for neutralizing the carboxyl groups contained in the binary ionomer resin and the ternary ionomer resin include sodium ions, potassium ions, lithium ions, zinc ions, calcium ions, magnesium ions, aluminum ions, and neodymium ions. Neutralization may be performed with two or more types of metal ions. Particularly preferred metal ions from the viewpoint of the resilience performance and durability of the golf ball 2 are sodium ions, zinc ions, lithium ions, and magnesium ions.
[0040] Specific examples of ionomer resins include trade names "Himilan 1555", "Himilan 1557", "Himilan 1605", "Himilan 1702", "Himilan 1706", "Himilan 1707", "Himilan 1855", "Himilan 1856", "Himilan 8150", "Himilan AM7311", "Himilan AM7315", "Himilan AM7317", "Himilan AM7327", "Himilan AM7329" and "Himilan AM7337" from Dow Mitsui Polychemicals; and trade names "Surlyn 6120" and "Surlyn 6910" from DuPont. ", "Surlyn 7930", "Surlyn 7940", "Surlyn 8140", "Surlyn 8150", "Surlyn 8940", "Surlyn 8945", "Surlyn 9120", "Surlyn 9150", "Surlyn 9320", "Surlyn 9910", "Surlyn 9945", "Surlyn AD8546", "HPF1000" and "HPF2000"; and ExxonMobil Chemical Company trade names "IOTEK7010", "IOTEK7030", "IOTEK7510", "IOTEK7520", "IOTEK8000" and "IOTEK8030". Two or more ionomer resins may be used in combination.
[0041] A preferred resin that can be used in combination with the ionomer resin is a styrene block-containing thermoplastic elastomer. The styrene block-containing thermoplastic elastomer has a polystyrene block as a hard segment and a soft segment. A typical soft segment is a diene block. Examples of the diene block compound include butadiene, isoprene, 1,3-pentadiene, and 2,3-dimethyl-1,3-butadiene. Butadiene and isoprene are preferred. Two or more compounds may be used in combination.
[0042] The styrene block-containing thermoplastic elastomer includes styrene-butadiene-styrene block copolymer (SBS), styrene-isoprene-styrene block copolymer (SIS), styrene-isoprene-butadiene-styrene block copolymer (SIBS), hydrogenated SBS, hydrogenated SIS, and hydrogenated SIBS. Hydrogenated SBS includes styrene-ethylene-butylene-styrene block copolymer (SEBS). Hydrogenated SIS includes styrene-ethylene-propylene-styrene block copolymer (SEPS). Hydrogenated SIBS includes styrene-ethylene-ethylene-propylene-styrene block copolymer (SEEPS).
[0043] The content of the styrene component in the styrene block-containing thermoplastic elastomer is preferably 1% by mass or more, more preferably 3% by mass or more, and particularly preferably 5% by mass or more, from the standpoint of the resilience performance of the golf ball 2. From the standpoint of the shot feel of the golf ball 2, this content is preferably 50% by mass or less, more preferably 47% by mass or less, and particularly preferably 45% by mass or less.
[0044] In the present invention, the styrene block-containing thermoplastic elastomer includes an alloy of one or more selected from the group consisting of SBS, SIS, SIBS, SEBS, SEPS, and SEEPS with an olefin. The olefin component in this alloy is presumed to contribute to improving compatibility with other base polymers. This alloy can contribute to the resilience performance of the golf ball 2. An olefin having a carbon number of 2 or more and 10 or less is preferred. Examples of suitable olefins include ethylene, propylene, butene, and pentene. Ethylene and propylene are particularly preferred.
[0045] Specific examples of polymer alloys include trade names "TEFABLOC T3221C", "TEFABLOC T3339C", "TEFABLOC SJ4400N", "TEFABLOC SJ5400N", "TEFABLOC SJ6400N", "TEFABLOC SJ7400N", "TEFABLOC SJ8400N", "TEFABLOC SJ9400N" and "TEFABLOC SR04" manufactured by Mitsubishi Chemical Corporation. Other specific examples of styrene block-containing thermoplastic elastomers include trade names "Epofriend A1010" manufactured by Daicel Chemical Industries, Ltd. and trade name "Septon HG-252" manufactured by Kuraray Co., Ltd.
[0046] The resin composition of the mid layer 6 may contain appropriate amounts of colorants, fillers, dispersants, antioxidants, UV absorbers, light stabilizers, fluorescent agents, fluorescent brighteners, etc. When the color of the golf ball 2 is white, a typical colorant is titanium dioxide.
[0047] The thickness Tm of the mid layer 6 is preferably 0.5 mm or greater and 2.0 mm or less. A golf ball 2 having a thickness Tm of 0.5 mm or greater has excellent resilience performance. From this viewpoint, the thickness Tm is more preferably 0.7 mm or greater, and particularly preferably 0.8 mm or greater. A golf ball 2 having a thickness Tm of 2.0 mm or less has excellent shot feeling. From this viewpoint, the thickness Tm is more preferably 1.5 mm or less, and particularly preferably 1.3 mm or less. The thickness Tm is measured directly under the land 12.
[0048] The hardness Hm of the mid layer 6 is preferably 50 or greater and 90 or less. A golf ball 2 having a hardness Hm of 50 or greater has excellent resilience performance. From this viewpoint, the hardness Hm is more preferably 55 or greater, and particularly preferably 60 or greater. A golf ball 2 having a hardness Hm of 90 or less has excellent shot feeling. From this viewpoint, the hardness Hm is more preferably 80 or less, and particularly preferably 75 or less.
[0049] The hardness Hm of the intermediate layer 6 is measured in accordance with the standard "ASTM-D 2240-68". The hardness Hm is measured using a Shore D hardness tester attached to an automatic hardness tester (H. Burleith Co., Ltd., trade name "Digitest II"). For the measurement, a sheet having a thickness of about 2 mm and made of the same material as the material of the intermediate layer 6, which is formed by a hot press, is used. Prior to the measurement, the sheet is stored at a temperature of 23°C for two weeks. When measuring, three sheets are stacked.
[0050] The flexural rigidity Fm of the mid layer 6 is preferably equal to or greater than 280 MPa. A golf ball 2 having a flexural rigidity Fm of 280 MPa or greater has excellent resilience performance. In this respect, the flexural rigidity Fm is more preferably equal to or greater than 290 MPa, and particularly preferably equal to or greater than 300 MPa. In respect of the shot feel of the golf ball 2, the flexural rigidity Fm is preferably equal to or less than 420 MPa, more preferably equal to or less than 400 MPa, and particularly preferably equal to or less than 380 MPa.
[0051] The bending rigidity Fm of the intermediate layer 6 is measured in accordance with the standard "JIS K 7106". A test piece having a thickness of 2 mm, a width of 20 mm, and a length of 100 mm is used for the measurement. Prior to the measurement, the test piece is kept in an environment of a temperature of 23±2° C. and a relative humidity of 50±5% for 14 days. The measurement conditions are as follows. Temperature: 23±2℃ Relative humidity: 50±5% Distance between supports: 50mm Bending speed: 60° / min Bending angles: 3°, 6°, 9° and 12° An example of a suitable tester for this measurement is the Olsen type rigidity tester manufactured by Toyo Seiki Seisakusho. Measurement results are plotted on a graph with the load scale on the vertical axis and the bending angle on the horizontal axis. The slope of the linear approximation curve of this plot is calculated, multiplied by 8.7078, and then divided by the cube of the thickness (cm) of the test piece to calculate the bending rigidity Fm.
[0052] The cover 8 is located outside the intermediate layer 6. In this embodiment, the cover 8 is in contact with the intermediate layer 6. The golf ball 2 may have an adhesive layer between the intermediate layer 6 and the cover 8. The cover 8 can be firmly bonded to the intermediate layer 6 via this adhesive layer. The cover 8 is molded from a resin composition. In this embodiment, the cover 8 is molded from a thermoplastic resin composition. Examples of the base polymer of this resin composition include ionomer resin, thermoplastic polyester elastomer, thermoplastic polyamide elastomer, thermoplastic polyurethane elastomer, thermoplastic polyolefin elastomer, and thermoplastic polystyrene elastomer. In particular, ionomer resin is preferable. Ionomer resin has high elasticity. The golf ball 2 having the cover 8 containing the ionomer resin has excellent resilience performance. This golf ball 2 has excellent flight performance in driver shots. The ionomer resin described above regarding the intermediate layer 6 can be used for the cover 8.
[0053] The ionomer resin may be used in combination with other resins. When used in combination, the ionomer resin is the main component of the base resin from the viewpoint of resilience performance. The amount P(I) of the ionomer resin in the base resin of the cover 8 is preferably 60 parts by weight or more, more preferably 65 parts by weight or more, and particularly preferably 70 parts by weight or more, per 100 parts by weight of the base resin. This amount P(I) is preferably 95 parts by weight or less, more preferably 90 parts by weight or less, and particularly preferably 85 parts by weight or less.
[0054] The resin composition of the cover 8 contains an ionomer resin neutralized with zinc ions. The cover 8 containing this ionomer resin is soft but is scratch-resistant. The zinc ion-neutralized ionomer resin can make up for the drawback of soft covers, which is poor abrasion resistance. Therefore, a low hardness can be adopted for the cover 8 containing the zinc ion-neutralized ionomer resin. This cover 8 can contribute to the spin performance and abrasion resistance of the golf ball 2.
[0055] From the standpoint of spin performance and abrasion resistance, the amount P(Zn) of the zinc ion-neutralized ionomer resin in the base resin of the cover 8 is preferably at least 60 parts by weight, more preferably at least 65 parts by weight, and particularly preferably at least 70 parts by weight, per 100 parts by weight of the base resin. This amount P(Zn) is preferably no more than 95 parts by weight, more preferably no more than 90 parts by weight, and particularly preferably no more than 85 parts by weight.
[0056] From the viewpoint of spin performance and abrasion resistance, the ratio of the amount P(Zn) of zinc ion neutralized ionomer resin to the amount P(I) of ionomer resin in the base resin of the cover 8 is preferably 90% or more, and particularly preferably 95% or more. This ratio is ideally 100%. The cover 8 may contain two or more types of zinc ion neutralized ionomer resins that differ from each other in hardness or fluidity.
[0057] Specific examples of zinc ion neutralized ionomer resins include the aforementioned product names "Himilan 1557", "Himilan 1702", "Himilan 1706", "Himilan 1855", "Himilan AM7327", "Himilan AM7329", "Surlyn 9120", "Surlyn 9150", "Surlyn 9320", "Surlyn 9945", "IOTEK7010", "IOTEK7030", "IOTEK7510" and "IOTEK7520".
[0058] In light of abrasion resistance, the amount P(Na) of the sodium ion-neutralized ionomer resin in the base resin of the cover 8 is preferably no more than 5 parts by weight per 100 parts by weight of this base resin. Ideally, this amount P(Na) is 0 part by weight.
[0059] The resin composition of the cover 8 may contain, together with the ionomer resin, a resin that can contribute to the fluidity of the cover. This cover 8 can be easily molded even if it is thin. Even if the thin cover 8 is soft, it does not impair the resilience performance of the golf ball 2. An example of a resin that can contribute to the fluidity is a binary copolymer of an olefin and an α,β-unsaturated carboxylic acid. This binary copolymer is not neutralized with metal ions. Another example of a resin that can contribute to the fluidity is a ternary copolymer of an olefin, an α,β-unsaturated carboxylic acid, and an α,β-unsaturated carboxylic acid ester. This ternary copolymer is not neutralized with metal ions. A resin having a melt flow rate of 25 g / 10 min or more is preferable.
[0060] The total amount P(n) of the binary copolymer and the terpolymer is preferably 10 parts by mass or more and 40 parts by mass or less per 100 parts by mass of the base resin of the cover 8. A cover 8 having a total amount P(n) of 10 parts by mass or more has excellent moldability. From this viewpoint, the total amount P(n) is more preferably 13 parts by mass or more, and particularly preferably 15 parts by mass or more. A cover 8 having a total amount P(n) of 40 parts by mass or less can contain a sufficient amount of zinc ion-neutralized ionomer resin. Furthermore, a cover 8 having a total amount P(n) of 40 parts by mass or less has excellent scratch resistance. From these viewpoints, the total amount P(n) is more preferably 35 parts by mass or less, and particularly preferably 30 parts by mass or less.
[0061] Specific examples of non-neutralized copolymers include those sold by Dow Polychemicals under the trade names "Nucrel N1050H", "Nucrel N2050H", "Nucrel N1110H" and "Nucrel N0200H" and those sold by Dow Chemical under the trade name "Primacol 5980I". Specific examples of non-neutralized copolymers include those sold by Dow Polychemicals under the trade names "Nucrel AN4318" and "Nucrel AN4319" and those sold by Dow Chemical under the trade names "Primacol AT310" and "Primacol AT320".
[0062] The resin composition of the cover 8 may contain appropriate amounts of colorants, fillers, dispersants, antioxidants, UV absorbers, light stabilizers, fluorescent agents, fluorescent brighteners, etc. When the color of the golf ball 2 is white, a typical colorant is titanium dioxide.
[0063] The thickness Tc of the cover 8 is preferably 0.50 mm or greater and 2.00 mm or less. A golf ball 2 having a thickness Tc of 0.50 mm or greater has excellent spin performance. From this viewpoint, the thickness Tc is more preferably 0.70 mm or greater, and particularly preferably 0.90 mm or greater. A golf ball 2 having a thickness Tc of 2.00 mm or less has excellent resilience performance. From this viewpoint, the thickness Tc is more preferably 1.50 mm or less, and particularly preferably 1.20 mm or less. The thickness Tc is measured directly under the land 12.
[0064] The cover 8 has a hardness Hc of 50 or less. This cover 8 can contribute to spin performance in approach shots. In this respect, the hardness Hc is more preferably 49 or less, and particularly preferably 48 or less. In terms of the resilience performance of the golf ball 2, the hardness Hc is preferably 30 or more, more preferably 35 or more, and particularly preferably 40 or more. The hardness Hc of the cover 8 is measured by the same method as the method for measuring the hardness Hm of the intermediate layer 6.
[0065] The flexural rigidity Fc of the cover 8 is preferably 80 MPa or less. A golf ball 2 having a flexural rigidity Fc of 80 MPa or less has excellent spin performance in approach shots. In this respect, the flexural rigidity Fc is more preferably 70 MPa or less, and particularly preferably 60 MPa or less. In respect of the resilience performance of the golf ball 2, the flexural rigidity Fc is preferably 20 MPa or more, more preferably 30 MPa or more, and particularly preferably 40 MPa or more. The flexural rigidity Fc of the cover 8 can be measured in the same manner as the flexural rigidity Fm of the intermediate layer 6.
[0066] The cover 8 preferably has a melt flow rate Mc of 8.0 g / 10 min or greater. The resin composition of the cover 8 has excellent fluidity. A thin cover 8 can be easily molded from this resin composition. From this viewpoint, the melt flow rate Mc is more preferably 9.0 g / 10 min or greater, and particularly preferably 10.0 g / 10 min or greater. The melt flow rate Mc is preferably 16.0 or less.
[0067] The melt flow rate Mc is measured in accordance with the standard "JIS K 7210-1:2014" under the following measurement conditions. Standard: Mass (A method) Temperature: 190℃ Load capacity: 2.16 kg Die: Standard An example of a device suitable for the measurement is Shimadzu Corporation's "Flow Tester CFT-100C."
[0068] This golf ball 2 satisfies the following formula (2). Mc*Tc ≧ 10.0 (2) In other words, the product (Mc*Tc) of the thickness Tc and the melt flow rate Mc of the cover 8 is 10.0 or greater. This cover 8 has excellent moldability despite its thinness. From the standpoint of moldability, the product (Mc*Tc) is more preferably 10.1 or greater, and particularly preferably 10.2 or greater. The product (Mc*Tc) is preferably 20.0 or less, more preferably 18.0 or less, and particularly preferably 16.0 or less.
[0069] This golf ball 2 satisfies the following formula (1). Fm / (Hm * Tm) - Fc / (Hc * Tc) ≧ 3.0 (1) In other words, the difference (Fm / (Hm*Tm)-Fc / (Hc*Tc)) is 3.0 or greater. In this golf ball 2, the mid layer 6 contributes to flight performance, and the cover 8 can contribute to spin performance. From this viewpoint, the difference (Fm / (Hm*Tm)-Fc / (Hc*Tc)) is more preferably 3.2 or greater, and particularly preferably 3.4 or greater. The difference (Fm / (Hm*Tm)-Fc / (Hc*Tc)) is preferably 6.0 or less, more preferably 5.5 or less, and particularly preferably 5.0 or less.
[0070] The amount of deformation Db of the golf ball 2 is preferably 2.5 mm or more and 4.0 mm or less. A golf ball 2 having a compressive deformation Db of 2.5 mm or more has an excellent shot feeling. From this viewpoint, the amount of deformation Db is more preferably 2.8 mm or more, and particularly preferably 3.0 mm or more. A golf ball 2 having a compressive deformation Db of 4.0 mm or less has excellent resilience performance. From this viewpoint, the amount of deformation Db is more preferably 3.7 mm or less, and particularly preferably 3.5 mm or less.
[0071] The aforementioned YAMADA compression tester "SCH" is used to measure the amount of compressive deformation Db. In this tester, the golf ball 2 is placed on a metal hard plate. A metal cylinder gradually descends towards the golf ball 2. The golf ball 2, sandwiched between the bottom of the cylinder and the hard plate, deforms. The distance traveled by the cylinder from a state in which an initial load of 98N is applied to the golf ball 2 to a state in which a final load of 1274N is applied, is measured. The speed at which the cylinder moves until the initial load is applied is 0.83mm / s. The speed at which the cylinder moves from the application of the initial load to the application of the final load is 1.67mm / s. EXAMPLES
[0072] [Example 1] 100 parts by mass of high cis polybutadiene (JSR Corporation's trade name "BR-730"), 27.7 parts by mass of zinc acrylate (Nisshoku Techno Fine Chemical Corporation's trade name "ZN-DA90S"), 10 parts by mass of zinc oxide (Toho Zinc Corporation's trade name "Ginrei R"), an appropriate amount of barium sulfate (Sakai Chemical Industry Co., Ltd.'s product number "BD"), 0.9 parts by mass of dicumyl peroxide (NOF Corporation's trade name "Percumyl D"), 3 parts by mass of benzoic acid (Tokyo Chemical Industry Co., Ltd., purity: 98% or more), and 1.2 parts by mass of pentachlorothiophenol zinc salt (Tokyo Chemical Industry Co., Ltd.) were kneaded to obtain a rubber composition. This rubber composition was placed in a mold consisting of an upper mold and a lower mold both having a hemispherical cavity and heated to obtain Core D having a diameter of 38.6 mm. The crosslinking temperature was 160°C. The crosslinking time was 20 minutes. The hardness distribution of this Core D is shown in Table 1 below.
[0073] 50 parts by mass of an ionomer resin (the aforementioned "Himilan AM7329"), 50 parts by mass of another ionomer resin (the aforementioned "Himilan 7337"), 6 parts by mass of barium sulfate, and 4 parts by mass of titanium dioxide were kneaded in a twin-screw kneading extruder to obtain a resin composition M1. A core was placed in a mold consisting of an upper mold and a lower mold, each of which had a hemispherical cavity. The molten resin composition M1 was injected around the core using an injection molding machine to form an intermediate layer. The thickness of this intermediate layer was 1.00 mm.
[0074] 35 parts by mass of ionomer resin (previously mentioned "Himilan 1855"), 40 parts by mass of another ionomer resin (previously mentioned "Himilan AM7327"), 25 parts by mass of non-neutralized binary copolymer (previously mentioned "Nucrel N1050H"), and 4 parts by mass of titanium dioxide were kneaded in a twin-screw kneading extruder to obtain a resin composition C2. A sphere consisting of a core and an intermediate layer was placed in a mold consisting of an upper mold and a lower mold each having a hemispherical cavity. The molten resin composition C2 was injected and coated around the sphere using an injection molding machine to form a cover. The thickness of this cover was 1.05 mm.
[0075] A clear paint based on two-component curing polyurethane was applied around the cover to obtain a golf ball of Example 1 having a diameter of about 42.7 mm and a mass of about 45.5 g.
[0076] [Examples 2-7 and Comparative Examples 1-13] Golf balls of Examples 2-7 and Comparative Examples 1-13 were obtained in the same manner as in Example 1, except that the specifications of the core, intermediate layer, and cover were as shown in Tables 6-9 below. The specifications of the core are shown in Tables 1 and 2 below. The composition of the intermediate layer is shown in Table 3 below. The composition of the cover is shown in Tables 4 and 5 below.
[0077] [Table 1]
[0078] [Table 2]
[0079] [Table 3]
[0080] [Table 4]
[0081] [Table 5]
[0082] [Scratch resistance] A sand wedge (Sumitomo Rubber Industries, Ltd., product name "XXIO12 (manufactured in 2021)", shaft hardness: R) was attached to a swing machine manufactured by Golf Laboratory. A golf ball was hit with this sand wedge at a head speed of 36 m / sec. The appearance of the cover was visually observed and rated based on the following criteria. Fe: Good IF: Splinters are visible. The results are shown in Tables 6-9 below.
[0083] [Moldability] The injection pressure of the injection molding machine was set to a value 10% lower to obtain golf balls. The appearance of the covers was visually observed and rated according to the following criteria. Fe(Ferior):Good IF(Inferior): Bears are seen. The results are shown in Tables 6-9 below.
[0084] [Flight performance] A driver (W#1, Sumitomo Rubber Industries' product name "XXIO1 (manufactured in 2021), shaft hardness: R) was attached to Golf Laboratory's swing machine. A golf ball was hit with this driver at a head speed of 40 m / sec, and the distance from the launch point to the rest point was measured. There was almost no wind at the time of the test. The average value of the flight distance obtained from the 12 measurements was calculated. Furthermore, this average value was ranked based on the following criteria. A: 199.0m or more B: 198.0m or more and less than 199.0m C: Less than 198.0m The results are shown in Tables 6-9 below.
[0085] [Spin performance] A sand wedge (Sumitomo Rubber Industries, Ltd., product name "XXIO12 (manufactured in 2021)", shaft hardness: R) was attached to Golf Laboratory's swing machine. A golf ball was hit with this sand wedge under conditions of a head speed of 16 m / sec. The golf ball was photographed continuously immediately after hitting, and the backspin speed was measured. The average value of the spin speed obtained from the 12 measurements was calculated. Furthermore, this average value was ranked based on the following criteria. A:2250rpm or more B: 2150 rpm or more and less than 2250 rpm C: Less than 2150 rpm The results are shown in Tables 6-9 below.
[0086] [comprehensive evaluation] The overall performance based on the abrasion resistance, moldability, flight performance and spin performance was rated according to the following criteria. A: There is no "IF" or "C", and the number of "B"s is 1 or 0. B: There is no "IF" or "C", and the number of "B"s is 2. C: There is "IF" or "C", and the total number of these is 1. D: There is “IF” or “C”, and the total number of these is 2 or more. The results are shown in Tables 6-9 below.
[0087] [Table 6]
[0088] [Table 7]
[0089] [Table 8]
[0090] [Table 9]
[0091] As shown in Tables 6 to 9, the golf balls of the respective Examples are excellent in overall performance. From these evaluation results, the superiority of the present invention is clear.
[0092] [Disclosure items] Each of the following sections discloses a preferred embodiment.
[0093] [Item 1] A golf ball comprising a core, a mid layer located outside the core and made of a resin composition, and a cover located outside the mid layer and made of another resin composition, A main component of a base resin of the resin composition of the intermediate layer is an ionomer resin, The cover has a cover hardness Hc (Shore D) of 50 or less, a base resin of the resin composition of the cover is mainly composed of an ionomer resin, an amount P(I) of an ionomer resin in a base resin of the cover is 60 parts by weight or more per 100 parts by weight of the base resin; an amount P(Na) of a sodium ion-neutralized ionomer resin in a base resin of the cover is 5 parts by mass or less per 100 parts by mass of the base resin; A golf ball that satisfies the following formulas (1) and (2). Fm / (Hm * Tm) - Fc / (Hc * Tc) ≧ 3.0 (1) Mc*Tc ≧ 10.0 (2) Hm: Hardness of the above intermediate layer (Shore D) Tm: thickness of the intermediate layer (mm) Fm: Bending rigidity of the above intermediate layer (Mpa) Tc: Thickness of the cover (mm) Fc: Bending rigidity of the cover (Mpa) Mc: Melt flow rate (g / 10min) of the above cover at a temperature of 190°C and a load of 2.16 kg
[0094] [Item 2] 2. The golf ball according to item 1, wherein the amount P(Zn) of the zinc ion-neutralized ionomer resin in the base resin of the cover is 60 parts by weight or more per 100 parts by weight of the base resin.
[0095] [Item 3] the base resin of the cover contains an unneutralized binary copolymer of an olefin and an α,β-unsaturated carboxylic acid, and / or an unneutralized ternary copolymer of an olefin, an α,β-unsaturated carboxylic acid, and an α,β-unsaturated carboxylic acid ester, 3. The golf ball according to item 1 or 2, wherein the total amount P(n) of the binary copolymer and the terpolymer is 10 parts by weight or more and 40 parts by weight or less per 100 parts by weight of the base resin.
[0096] [Item 4] 4. The golf ball according to any one of items 1 to 3, wherein the difference (Hs-Ho) between the surface hardness Hs (Shore C) of the core and the center hardness Ho (Shore C) of the core is 28 or greater.
[0097] [Item 5] 5. The golf ball according to any one of items 1 to 4, wherein the intermediate layer has a bending rigidity Fm of 300 MPa or more, and the cover has a bending rigidity Fc of 60 MPa or less.
[0098] [Item 6] 6. The golf ball according to any one of items 1 to 5, wherein the cover has a thickness Tc of 1.20 mm or less.
[0099] [Item 7] 7. The golf ball according to any one of items 1 to 6, wherein the cover has a melt flow rate, Mc, of 8.0 g / 10 min or more.
[0100] [Item 8] Item 2. The golf ball according to item 1, wherein the ratio of the amount P(Zn) of zinc ion-neutralized ionomer resin to the amount P(I) of the ionomer resin in the base resin of the cover is 90% or greater.
[0101] [Item 9] Item 2. The golf ball according to item 1, wherein the base resin of the cover comprises a first zinc ion neutralized ionomer resin and a second zinc ion neutralized ionomer resin.
[0102] [Item 10] A golf ball comprising a core, a mid layer located outside the core and made of a resin composition, and a cover located outside the mid layer and made of another resin composition, the cover having a thickness Tc of 1.20 mm or less and a hardness Hc (Shore D) of 50 or less, A main component of a base resin of the resin composition of the intermediate layer is an ionomer resin, a base resin of the resin composition of the cover is mainly composed of an ionomer resin, an amount P(I) of an ionomer resin in a base resin of the cover is 60 parts by weight or more per 100 parts by weight of the base resin; a ratio of an amount P(Zn) of zinc ion-neutralized ionomer resin to an amount P(I) of the ionomer resin in a base resin of the cover is 90% or greater; A golf ball that satisfies the following formulas (1) and (2). Fm / (Hm * Tm) - Fc / (Hc * Tc) ≧ 3.0 (1) Mc*Tc ≧ 10.0 (2) Hm: Hardness of the above intermediate layer (Shore D) Tm: thickness of the intermediate layer (mm) Fm: Bending rigidity of the above intermediate layer (Mpa) Tc: Thickness of the cover (mm) Fc: Bending rigidity of the cover (Mpa) Mc: Melt flow rate (g / 10min) of the above cover at a temperature of 190°C and a load of 2.16 kg
[0103] [Item 11] Item 11. The golf ball according to item 10, wherein the ratio of the amount P(Zn) to the amount P(I) is 100%. [Industrial Applicability]
[0104] The golf ball described above is suitable for playing on a golf course, practicing at a driving range, and the like. [Explanation of symbols]
[0105] 2. Golf ball 4. Core 6. Middle tier 8. Cover 10 Dimples 12···Rand
Claims
1. A golf ball comprising a core, a mid layer located outside the core and made of a resin composition, and a cover located outside the mid layer and made of another resin composition, A main component of a base resin of the resin composition of the intermediate layer is an ionomer resin, the cover has a hardness Hc (Shore D) of 50 or less; a base resin of the resin composition of the cover is mainly composed of an ionomer resin, an amount P(I) of an ionomer resin in a base resin of the cover is 60 parts by weight or more per 100 parts by weight of the base resin, an amount P(Na) of a sodium ion-neutralized ionomer resin in a base resin of the cover is 5 parts by mass or less per 100 parts by mass of the base resin; A golf ball that satisfies the following formulas (1) and (2). Fm / (Hm * Tm) - Fc / (Hc * Tc) ≧ 3.0 (1) Mc*Tc≧10.0 (2) Hm: hardness of the intermediate layer (Shore D) Tm: thickness of the intermediate layer (mm) Fm: bending rigidity of the intermediate layer (Mpa) Tc: thickness of the cover (mm) Fc: bending rigidity of the cover (Mpa) Mc: Melt flow rate (g / 10 min) of the cover at a temperature of 190° C. and a load of 2.16 kg
2. 2. The golf ball according to claim 1, wherein an amount P(Zn) of the zinc ion-neutralized ionomer resin in the base resin of the cover is 60 parts by weight or more per 100 parts by weight of the base resin.
3. the base resin of the cover contains an unneutralized resin which is a binary copolymer of an olefin and an α,β-unsaturated carboxylic acid, and / or an unneutralized resin which is a ternary copolymer of an olefin, an α,β-unsaturated carboxylic acid, and an α,β-unsaturated carboxylic acid ester, 3. The golf ball according to claim 1, wherein the total amount P(n) of the binary copolymer and the terpolymer is 10 parts by weight or more and 40 parts by weight or less per 100 parts by weight of the base resin.
4. 3. The golf ball according to claim 1, wherein the difference (Hs-Ho) between the surface hardness Hs (Shore C) of the core and the center hardness Ho (Shore C) of the core is 28 or greater.
5. 3. The golf ball according to claim 1, wherein the intermediate layer has a flexural rigidity Fm of 300 MPa or more, and the cover has a flexural rigidity Fc of 60 MPa or less.
6. 3. The golf ball according to claim 1, wherein the cover has a thickness Tc of 1.20 mm or less.
7. 3. The golf ball according to claim 1, wherein the cover has a melt flow rate Mc of 8.0 g / 10 min or greater.
8. 2. The golf ball according to claim 1, wherein a ratio of an amount P(Zn) of zinc ion-neutralized ionomer resin to an amount P(I) of the ionomer resin in the base resin of the cover is 90% or greater.
9. 2. The golf ball of claim 1, wherein the base resin of the cover comprises a first zinc ion neutralized ionomer resin and a second zinc ion neutralized ionomer resin.
Citation Information
Patent Citations
Golf ball
JP2023004542A